Isolation and Multiple Differentiation of Rat Pericardial Fluid Cells - Sun, Ying; Wang, Yan; Li, Zongjin; Guo, Zhikun (Frontiers in Cell and Developmental Biology, 2021)
Objective: The aim of present study is to isolate and analyze the characterization of pericardial fluid cells (PFCs) from rat and provides a morphological basis for the basic research and clinical application of PFCs. Methods: After aseptic thoracotomy was performed, normal saline was injected into the pericardial cavity of 50 adult Sprague–Dawley rats. The mixture of diluted pericardial fluid was extracted, centrifuged, and cultured. The cell morphology of different generations in the pericardial fluid was observed on an inverted microscope. The expression levels of CD44, CD29, CD90, and pan-hematopoietic marker CD45 were analyzed via flow cytometry. The third-generation cells were used for osteogenic, adipogenic, and cardiac differentiation. Results: PFCs were successfully isolated and subcultured. PFCs were predominantly circular in shape after 24 h of culture. Following subculture for 3 days, the cells demonstrated a spindle shape. The rat pericardial fluid contains cell populations with uniform morphology, good growth state, and strong proliferation ability. Flow cytometry results showed that CD29 (100%) and CD90 (99.3%) were positively expressed, whereas CD45 (0.30%) and CD44 (0.48%) were negatively expressed. The PFCs could differentiate into osteoblasts and adipocytes after being induced. Cardiac differentiation also was confirmed by cardiac troponin T (cTnT) and α-sarcomeric actin (α-SA) staining. Conclusion: This study revealed that a subpopulation of cells was isolated from pericardial fluid, which exhibited progenitor cell features and multiple differentiation potency. PFCs could serve as an alternative cell source for myocardial tissue repair, engineering, and reconstruction.